Abuse-Deterrent Opioid Formulations and the Opioid Crisis: A Pharmacist's Perspective. Issue 1 (February 2021) - Gadd, Shannon; Cox, Nicholas; Samuelson, James; Kenney, Amy; Turner, Kyle; Cochran, Gerald
Abstract : Background: For over 20 years, the United States has suffered the detrimental effects of an opioid epidemic. Extended-release opioid products are particularly prone to abuse due to the high amount of opioid present. By bypassing the controlled-release mechanisms and nonoral administration, individuals experience intense and dangerous "highs." Abuse-deterrent opioid formulations have been recommended as a potential solution to the crisis, but widespread utilization has been stunted and their role in therapy remains unclear owing to limited real-world efficacy data and affordability issues. This review discusses abuse-deterrent opioid formulations, the mechanisms and data underlying available products, and a pharmacist's perspective of their role in the opioid crisis. Methods: The authors reviewed PubMed, MEDLINE, and Google Scholar electronic databases for premarketing and postmarketing studies on OxyContin, Xtampza ER, and Hysingla ER. Results: Studies showed lower rates of abuse (19% reduction), opioid use disorder (27%), overdose (34%), and fatalities (85%) with the reformulated OxyContin when compared with the original product and comparator opioids. However, these studies revealed the potential for bypassing abuse-deterrent mechanisms and diverting abuse to other drugs. Postmarketing studies are unavailable for Xtampza ER or Hysingla ER, although premarketing studies suggested that some controlled-release properties persist when the product is manipulated, indicating that abuse may be more difficult and less rewarding. Conclusions: Abuse-deterrent opioid products may lead to reductions in abuse, overdose, and overdose fatalities. However, cost, loopholes in deterrence mechanism, and possible diversion to other substances hinder their role in the opioid crisis. Multiple approaches must be used to improve opioid safety, and further postmarketing and real-world analyses should be performed on available opioid formulations to assess their impact on abuse-related adverse events.